Mechanisms of depression: the role of neurogenesis - Henn, Fritz A.; Vollmayr, Barbara; Sartorius, Alexander (Drug discovery today. Disease mechanisms, 2004)
The behavioral changes in depression can relate to alterations in hippocampal function. A variety of inputs to the hippocampus can effect mood, including norepinephrine (NE), serotonin (5HT) and cortisol, all factors activated by stress. These are thought to act through activation of CREB and neurotrophins such as BDNF. Stress has been shown to decrease hippocampal neurogenesis and most antidepressants increase neurogenesis, leading to the hypothesis that changes in the rate of new neuron formation might underlie depressive illnesses.
Gesehen am 10.11.2020